An optimal path planning problem for heterogeneous multi-vehicle systems - Klaučo, Martin; Blažek, Slavomír; Kvasnica, Michal (Zielona Góra: Uniwersytet Zielonogórski)
A path planning problem for a heterogeneous vehicle is considered. Such a vehicle consists of two parts which have the ability to move individually, but one of them has a shorter range and is therefore required to keep in a close distance to the main vehicle. The objective is to devise an optimal path of minimal length under the condition that at least one part of the heterogeneous system visits all desired waypoints exactly once. Two versions of the problem are considered.
Keywords: path planning; multi-vehicle system; mixed-integer programming